Innovation of a Flattening Tool for Optimizing the Water Hyacinth Weaving Process at Maeswara Basket: A Preliminary Study and Technology Implementation - Kholifah, Nur; Triyanto; Elvera, Resi Sepsilia; Nurtanto, Muhammad; Eko Wibowo, Aris; Mutohhari, Farid; satya, Danang; Cintiara Kinanti, Tabita (International Journal of Community Service Learning, 2024)
Maeswara Basket faces problems with manual flattening tools that are ineffective in producing crafts from water hyacinth fibre. The proposed solution is developing a flattening tool by considering ergonomics, work safety, speed settings, and primary controls features. This study uses a community-based research (CBR) approach with five stages: problem identification, literature analysis, design planning, manufacturing, and evaluation. Six people assessed the flattening tool based on ease of use, process efficiency, quality of results, and overall evaluation using a Likert scale of 1-5. The results showed that the tool met important criteria such as ergonomics, ease of operation, flattening speed, thickness consistency, quality of results, and component durability, with scores ranging from 4.3 to 4.8 out of 5.0, categorized as "very satisfactory." The new tool excels in ease of use, process efficiency, and quality of results, with the main features of speed settings and controls that maintain the stability of fibre size during the flattening process. This study contributes to the development of products according to community needs. It has the potential to increase the production capacity of water hyacinth artisans, with opportunities for further development using automation technology.